Quality of life in primary school: Music in the classrooms - Vernia-Carrasco, Ana Mercedes (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Music training and education in future teachers is not only aimed at teaching and learning music, but also at using music as a tool in the classroom. The proposed objectives are the following: (i) to know the quality of life of the students, future teachers and teachers; (ii) to know the impact of musical education and training in improving the quality of life in future teachers, and (iii) to propose a dossier of musical activities in the classroom to improve the quality of life.